2019
DOI: 10.3345/kjp.2018.06814
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly growing pediatric trampoline-related injuries in Korea: a 10-year single center retrospective study

Abstract: PurposeSeveral published policy statements have warned against the risks associated with trampoline use and recommended safety guidelines. However, few studies have focused on trampoline-related injuries in Korea. This study aimed to assess the incidence and characteristics of pediatric trampoline-related injuries presented to Ulsan University Hospital.MethodsWe retrospectively reviewed the medical records of children aged <16 years with trampoline-related injuries who visited our Emergency Department between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Sixty-nine studies were duplicates, leaving 87 studies for review of titles and abstracts. Of these, 16 articles [10,11,[16][17][18][19][20][21][22][23][24][25][26][27][28][29] were relevant and the full papers were retrieved.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sixty-nine studies were duplicates, leaving 87 studies for review of titles and abstracts. Of these, 16 articles [10,11,[16][17][18][19][20][21][22][23][24][25][26][27][28][29] were relevant and the full papers were retrieved.…”
Section: Resultsmentioning
confidence: 99%
“…Seventy-one studies were deleted under exclusion criteria; 3, 14, 6, 5, 37 and 6 studies were other intervention, no outcomes, biomechanics, review, other injuries and no English language, respectively. Sixteen studies were included for the analysis of trampoline-related injury; 14 studies [16][17][18][19][20][21][22][23][24][25][26][27][28][29] were retrospective cohort and 2 studies [10,11] were comparative cohort studies. All 14 studies reported conservative and surgical management.…”
Section: Resultsmentioning
confidence: 99%
“…4,9 Trampolines have become an increasingly popular activity over the past decade with many reports citing an increase in trampoline related injuries globally. [10][11][12] To determine whether there has been a change in children's activities from previous studies with trampoline related injuries causing a large proportion of flexion-type supracondylar fractures, a multi-hospital study with larger sample size is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the incidence of proximal tibial metaphyseal fractures was rare, but has increased as the trampoline has become more popular. [4][5][6] However, the proximal tibial metaphyseal fracture caused by TRI differs from that of non-TRI in both the initial angular deformities and the patient's recovery. In the past, proximal tibial metaphyseal fractures were reported to have clinical importance because of the possibility of tibial valgus deformity after trauma, 7,14 and angular deformity might progress after bone union.…”
Section: Angular Deformities On the Coronal Planementioning
confidence: 99%
“…Proximal tibial metaphyseal fracture was relatively rare in 1980s, but with the recent popularization of trampoline activities, its incidence as one of trampoline-related injuries (TRIs) has increased, especially among children aged under six years. [1][2][3][4][5][6] Some studies have reported that proximal tibial metaphyseal fracture has a risk of post-traumatic valgus deformity. 7,8 However, it is currently suggested that the degree of valgus deformity would be minimal or absent in patients with proximal metaphyseal fracture by TRI.…”
Section: Introductionmentioning
confidence: 99%